2022
DOI: 10.3390/molecules27051503
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry: Chemical Composition, Antioxidant Activity and Impact on Human Health: Overview

Abstract: Cranberries are a rich source of bioactive compounds that comprise a healthy diet. Cranberry is abundant in nutritional components and many bioactive compounds that have antioxidant properties. Both American (Vaccinium macrocarpon) and European (Vaccinium oxycoccus) cranberry species are rich in polyphenols such as phenolic acids, anthocyanins and flavonoids, and is one of the few fruits that is high in proanthocyanidins, which is linked to many health benefits. The review systematizes information on the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 93 publications
(269 reference statements)
1
57
0
Order By: Relevance
“…Triterpenoids identified in cranberry fruit are responsible for their anti-inflammatory, antitumor, and anticancer effects [ 41 ]. Chen et al found that phytosterols lower blood cholesterol levels [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triterpenoids identified in cranberry fruit are responsible for their anti-inflammatory, antitumor, and anticancer effects [ 41 ]. Chen et al found that phytosterols lower blood cholesterol levels [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total amount of proanthocyanidins had a strong positive correlation with the antiradical activity determined by the ABTS method and the reducing activity determined by the FRAP method (r = 0.781, p < 0.001 and r = 0.726, p < 0.001, respectively). Proanthocyanidins identified in cranberry fruit samples contain epicatechin units in their structure, which have exceptionally strong antioxidant properties [ 41 , 59 ]. The strong antioxidant properties are possibly due to proanthocyanidins have more hydroxyl groups, which act as strong hydrogen donors, to receive free radicals and free radicals generated by itself form stable intramolecular hydrogen bonds with semi-quinoid free radicals and o-quinones, and thus block the chain reaction of free radicals [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the toxicity of PAC-As, we have recently observed that when tested for effects on the viability of human cells, different purified PAC-As were found to be safe with noteworthy low cytotoxicity values [ 286 ]. Moreover, from this perspective, the widespread use of different formulations of dried cranberry extracts, naturally rich in PAC-As [ 146 ], for the prevention of urinary tract infections (UTIs) sustains the high safety profile of PAC-As-containing products to develop broad-spectrum antiviral agents of natural origin suitable to prevent infections [ 287 , 288 ]. Interestingly, the antibacterial activity of PAC-As could be valuable also for the prevention of bacterial superinfections of the respiratory tract that may follow viral RTIs (due to both virus- and immune-mediated damage of the respiratory mucosa).…”
Section: Discussionmentioning
confidence: 99%
“…The active ingredients with beneficial effects on kidney disease are extracted from cranberry fruits, which have a dark red color. They contain significant amounts of vitamin C, salicylic acid, and antioxidants called anthocyanins and proanthocyanins (Nemzer et al, 2022).…”
Section: Cranberry: a Brief Overviewmentioning
confidence: 99%
“…Most of these are concentrated in the peel and are reduced by the preparation of cranberry juice. Cranberries contain quercetin, myricetin, peonidine, ursolic acid, and PACs type‐A (Nemzer et al, 2022). Anthocyanins and other flavonoids can reduce lipid oxidation and protein glycosylation; thus, cranberry juice could help reduce the side effects of diabetes and improve the quality of life of people with this condition (Bendokas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%